Lucerne quality and possibilities for its estimation - Kirilov A. (Quality in lucerne and medics for animal production, 2001)
Lucerne quality is examined in the article as a generalizing concept covering forage chemical, morphological and physical composition, digestibility, intake, energy and protein value. Classical methods and some non-conventional approaches for evaluation of quality characteristics in lucerne are mentioned in a summarized form. Quality Index (QI) calculated on the basis of the net energy ingested with the forage when fed ad libitum in relation to that necessary for life maintenance and Index of Protein Value (IPV) calculated on the basis of the protein digestible in intestines (PDI) ingested with the forage in relation to the needs for maintenance are described. As complex characteristics for the feeding value of lucerne they stand closer to real nutritive value of forage. The relation of QI and IPV with the mean stage of development in lucerne (MSW) shows that they are predictable characteristics and can participate in mathematical models for lucerne quality prediction.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)